The Arabidopsis GASA10 gene encodes a cell wall protein strongly expressed in developing anthers and seeds. (July 2017) - Trapalis, Menelaos; Li, Song Feng; Parish, Roger W.
Highlights: GASA10 gene is primarily expressed in developing anthers and seeds. GASA10 protein is located in the cell wall. Over-expressing GASA10 results in reduced silique elongation. GASA10 protein expressed in vitro does not possess antimicrobial activity. Abstract: The Arabidopsis GASA10 gene encodes a GAST1-like (Gibberellic Acid-Stimulated) protein. Reporter gene analysis identified consistent expression in anthers and seeds. In anthers expression was developmentally regulated, first appearing at stage 7 of anther development and reaching a maximum at stage 11. Strongest expression was in the tapetum and developing microspores. GASA10 expression also occurred throughout the seed and in root vasculature. GASA10 was shown to be transported to the cell wall. Using GASA1 and GASA6 as positive controls, gibberellic acid was found not to induce GASA10 expression in Arabidopsis suspension cells. Overexpression of GASA10 ( 35S promoter-driven) resulted in a reduction in silique elongation. GASA10 shares structural similarities to the antimicrobial peptide snakin1, however, purified GASA10 failed to influence the growth of a variety of bacterial and fungal species tested. We propose cell wall associated GASA proteins are involved in regulating the hydroxyl radical levels at specific sites in the cell wall to facilitate wall growth (regulating cell wall elongation).